Adolescence and reproductive health problem - Cervantes Begazo, René (2015)
In early adolescence secondary sexual characters appear, a somatic growth spurt occurs, menstruation and ovulation in women and sperm maturation and ejaculatory ability in men appears. Fertility in both sexes is reached. Also occur in adolescence, psycho-emotional changes of great variability and significance.